Structural and functional characterisation of the fungal plasma membrane proton pump, Pma1, and related P-Type ATPases - Geurts, MMG (2022)
P-type ATPases are a large family of ubiquitous ion pumps that carry out fundamental biological processes, ranging from generating membrane potentials to muscle contraction.